Experimental and Clinical Metastasis A Comprehensive Review - Burnier, Julia V.; Burnier, Miguel N.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The primary cause of death related to cancers can be traced back to metastases, originated from cancer cells. The presence of metastatic disease, the spread of cancer cells, is the most important prognostic and survival factor in patients with cancer. Although treatment of the primary tumor is well established and usually results in local control, treating metastatic disease is a much more daunting task. At diagnosis, few patients present with clinically detectable metastatic lesions regardless of the clinical prognostic factor. Clinical trials assessing potential therapeutic agents are important in order to define the best specific treatment for a particular patient, which are the basis for patient-oriented research that eventually lead to personalized medicine. This volume aims to comprehensively present the latest research and information about metastasis. Understanding the mechanisms underlying the metastatic phenomenon could have vast implications for the large number of patients who are at a high risk for the development of metastasis.
Introduction -- Interactions of Normal Tissues and Systems with Metastatic Cells: Impact on Location, Survival and Growth -- Introduction to Metastasis Suppressor Genes -- Metastasis suppressor genes -- Metastatic Dormancy & Metastatic Suppressor Genes -- Clinical Implications -- Growth Factor Systems and Cell Cycle Regulation -- Angiogenesis -- Inflammatory mediators in Tumorigenesis and Metastasis -- Role of stroma in disease progression -- Local spread -- Lymphatic – GI tract and Breast Cancer -- Hematogenous – Uveal Melanoma -- Other methods -- Haematogenous Models of Metastases -- Spontaneous, Induced, and Transgenic Models of Metastasis -- Orthotopic and Ectopic Models of Metastasis -- Animal Model Imaging Techniques -- Diagnosis of Metastasis -- Cancer Staging -- Diagnostic Immunohistochemistry in Tumor metastasis -- Genomics and Proteomics -- The role of chemotherapy for metastatic disease -- Integrating chemotherapy to surgery: Novel approaches in regionally aggressive cancer metastasis -- Palliative radiation therapy -- Role of Surgery in the Diagnosis and Management of Metastatic Cancer -- Prerequisite genetic traits for metastasis -- Metastasis Initiation -- Index.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.